Methods of Automated Monitoring and Control System of Greenhouse Complex - Dolhosheia, I.; Tsymbal, O. (My University, 2025)
The study considers methods of an automated monitoring and control system for a greenhouse complex aimed at increasing production efficiency and optimizing resource consumption. The proposed mathematical models describe the dynamics of the main microclimate parameters, in particular temperature, humidity, CO₂ concentration and soil moisture, which allows for precise process control. Based on the obtained models, a decision-making logic was built that combines threshold rules, fuzzy logic and adaptive control, ensuring flexibility and reliability in changing conditions. The numerical simulation demonstrated the system's ability to maintain stable environmental parameters with minimizing energy costs and water consumption. The results confirm that the implementation of such systems contributes to increasing yields, improving product quality and sustainable development of the agricultural sector in the conditions of Industry 4.0 and Industry 5.0.
Keywords: greenhouse complex; fuzzy logic; microclimate